Matching stage strategy development of PT Alam Sutera Realty Tbk: Diversification as key strategy for business sustainability - Gunawan, William Ben (Universitas Pendidikan Nasional, 2024)
This study investigated the strategic development of PT Alam Sutera Realty Tbk (ASRI), focusing on diversification as a key strategy for business sustainability amidst issues of undervalued stock and unstable financial performance. A comprehensive analysis of external and internal factors was conducted using frameworks such as PESTLE, Porter’s 5 Forces, Internal-External Matrix, TOWS Matrix, SPACE Matrix, Grand Strategy Matrix, Quantitative Strategic Planning Matrix (QSPM), Blue Ocean Recommendation, and Balanced Scorecard. The findings indicated that ASRI scored 3.21 on the Internal Factor Evaluation (IFE) and 3.29 on the External Factor Evaluation (EFE), placing it in the